Panama : Technical Assistance Report-Monetary and Financial Statistics. (IMF Staff Country Reports; Country Report ;, 2021)
At the request of the Superintendency of Banks of Panama (SBP), and with the support of the International Monetary Fund's (IMF's) Western Hemisphere Department (WHD), a monetary and financial statistics (MFS) remote technical assistance (TA) mission from the IMF's Statistics Department (STA) took place during June 22-July 10, 2020. The main objective of the mission was to assist the SBP in the compilation of new standard report forms for depository corporations (SRF 1SR and SRF 2SR) on the basis of internationally accepted standards, as set out in the IMF's 2016 Monetary and Financial Statistics Manual and Compilation Guide (MFSMCG), following the introduction of a new chart of accounts by the SBP, and to agree on an improved timeline to report monetary and financial statistics to STA, on a monthly basis. The work of the mission was facilitated by the excellent collaboration of the staff of the Financial Studies Directorate (FSD) of the SBP. The officials met during the mission are listed in Appendix I.